2017
DOI: 10.1002/jbio.201700028
|View full text |Cite
|
Sign up to set email alerts
|

Developing Raman spectroscopy as a diagnostic tool for label‐free antigen detection

Abstract: For several decades, a multitude of studies have documented the ability of Raman spectroscopy (RS) to differentiate between tissue types and identify pathological changes to tissues in a range of diseases. Furthermore, spectroscopists have illustrated that the technique is capable of detecting disease-specific alterations to tissue before morphological changes become apparent to the pathologist. This study draws comparisons between the information that is obtainable using RS alongside immunohistochemistry (IHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Some online process controls implementing PAT are nowadays carried out with Raman spectroscopy measurements in cell culture cultivations (Abu-Absi et al, 2011; Lewis et al, 2018; Nagy et al, 2018). Esmonde-White et al found that Raman spectroscopy is already applied in GMP facilities (good manufacturing practice) for monoclonal antibody (mAB) production (Esmonde-White et al, 2017).…”
Section: Achievements In Continuous Upstream Applications With E Colimentioning
confidence: 99%
“…Some online process controls implementing PAT are nowadays carried out with Raman spectroscopy measurements in cell culture cultivations (Abu-Absi et al, 2011; Lewis et al, 2018; Nagy et al, 2018). Esmonde-White et al found that Raman spectroscopy is already applied in GMP facilities (good manufacturing practice) for monoclonal antibody (mAB) production (Esmonde-White et al, 2017).…”
Section: Achievements In Continuous Upstream Applications With E Colimentioning
confidence: 99%
“…To date, Raman and FTIR have provided the biochemical fingerprint of the genome, metabolome and proteome of biological samples under distinct conditions, delivering biochemical images and allowing researchers to detect molecular pathological changes with high accuracy. Their use has been successful for diagnosing diseases such as Alzheimer’s, dementia [ 12 , 13 ], diabetes [ 14 , 15 ], viral infections [ 16 , 17 , 18 , 19 ], and cancer [ 20 , 21 , 22 , 23 ], or for identifying bacteria and fungi infecting patients (guiding physicians regarding treatment choices) [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%